Dietary Exercise as a Novel Strategy for the Prevention and Treatment of Metabolic Syndrome: Effects on Skeletal Muscle Function - Aoi, Wataru (Hindawi Publishing Corporation, 2011)
A sedentary lifestyle can cause metabolic syndrome to develop. Metabolic syndrome is associated with metabolic function in the skeletal muscle, a major consumer of nutrients. Dietary exercise, along with an adequate diet, is reported to be one of the major preventive therapies for metabolic syndrome; exercise improves the metabolic capacity of muscles and prevents the loss of muscle mass. Epidemiological studies have shown that physical activity reduces the risk of various common diseases such as cardiovascular disease, diabetes, and cancer; it also helps in reducing visceral adipose tissue. In addition, laboratory studies have demonstrated the mechanisms underlying the benefits of single-bout and regular exercise. Exercise regulates the expression/activity of proteins associated with metabolic and anabolic signaling in muscle, leading to a change in phenotype. The extent of these changes depends on the intensity, the duration, and the frequency of the exercise. The effect of exercise is also partly due to a decrease in inflammation, which has been shown to be closely related to the development of various diseases. Furthermore, it has been suggested that several phytochemicals contained in natural foods can improve nutrient metabolism and prevent protein degradation in the muscle.